CORPORATE DETERMINANTS OF DIVIDEND POLICY: EMPIRICAL EVIDENCE FROM MALAYSIAN PUBLIC LISTED FIRMS - Cleopatra Leai, Suel; Chee Ling, Chin (UNIMAS Publisher, 2025)
This study investigates the determinants of dividend policy among 30 firms listed on the FTSE Bursa Malaysia KLCI (FBMKLCI) from 2015 to 2023. Drawing on signaling theory and agency cost theory, the analysis examines the influence of liquidity, profitability and leverage on dividend payout ratios (DPR). Using pooled OLS regression with robust standard errors, the results reveal that control variable of growth opportunities have a significant and positive effect on dividend payout, suggesting that Malaysian firms use dividends as a credible signal of financial strength and future prospects. In contrast, liquidity, profitability, and leverage are statistically insignificant, indicating that these financial factors are not the primary drivers of dividend decisions among large-cap firms. The findings extend existing evidence from emerging markets and also provides practical insights for managers, investors, and policymakers in developing dividend strategies that enhance market confidence and shareholder value.